REVIEWING THE PROPERTIES OF RARE EARTH ELEMENT-BEARING MINERALS, RARE EARTH ELEMENTS AND CERIUM OXIDE COMPOUND - Tatang Wahyudi (Indonesian Mining Journal, 2015)
Of the 17 rare earth elements (REEs), 15 belong to the chemical group called lanthanides, plus yttrium and scandium. The lanthanides consist of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and lutetium. Cerium is one of the most abundant REEs, comprises more of the earth’s crust than copper or lead. At least, there are 29 potential REE-bearing minerals. Basnasite, monazite and xenotime are among them and serve as the most exploited minerals. The REEs are mostly applied for high technology application such as computer, telecommunication, nuclear and sophisticated instruments for exploring the outer space.